2021
DOI: 10.1111/ijfs.15367
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and interaction mechanism of ovalbumin‐based nanocarriers for metallic ion encapsulation

Abstract: Ovalbumin (OVA), due to its desirable physiochemistry properties and biocompatibility, has been widely adopted as bioactive compound carriers in the field of pharmacy and food. This study explored the interaction patterns between OVA and three flavonoids, namely naringin, hesperidin and anthocyanin, and the possibilities of OVA-flavonoid complexes as nanocarriers that entrap mineral substances. Results showed that ovalbumin interacts with three flavonoids through hydrophobic interaction and hydrogen bonding. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Ovalbumin is the most abundant egg white protein (EWP), accounting for more than 50% of the total proteins [ 18 ]. Several studies have demonstrated the use of ovalbumin as nanogels and nanocarriers when combined with surfactants, metal ions, and chitosan [ 19 , 20 , 21 ]. Notably, the ovalbumin epitope, SIINFEKL, which has been extensively used for immune stimulation, was reported to self-assemble to form a stable hydrogel [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ovalbumin is the most abundant egg white protein (EWP), accounting for more than 50% of the total proteins [ 18 ]. Several studies have demonstrated the use of ovalbumin as nanogels and nanocarriers when combined with surfactants, metal ions, and chitosan [ 19 , 20 , 21 ]. Notably, the ovalbumin epitope, SIINFEKL, which has been extensively used for immune stimulation, was reported to self-assemble to form a stable hydrogel [ 22 ].…”
Section: Introductionmentioning
confidence: 99%